Electrolytic adhesive, preparation method and application thereof, and adhesive tape

The electrolytic adhesive formed by copolymerization of reactive conductive salts and polymer monomers has solved the problem of insufficient adhesion before power on and residual after power on, and achieved improvements in high adhesion and aging resistance.

CN119875545APending Publication Date: 2025-04-25NADIAN (GUANGDONG) MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510276945.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing electrolytic adhesive has poor adhesion before powering on, and there will be obvious residue on the patch after powering on.

Method used

The electrolytic adhesive is formed by copolymerizing the reactive conductive salt with polymer monomer, which increases its adhesiveness and aging resistance, and achieves easy peeling by applying a voltage.

Benefits of technology

The adhesive force, stickiness, shear force and cohesion of electrolytic adhesives are improved, and the residue after power-on is reduced, achieving aging resistance and impact resistance during the storage and use of parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The invention relates to an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, and relates to the technical field of adhesives, the electrolytic adhesive is formed by a copolymerization reaction of a reactive conductive salt and a polymer monomer; based on 100 parts by weight of the polymer monomer, the addition amount of the reactive conductive salt is 0.5-25 parts by weight. The electrolytic adhesive provided by the invention has high adhesive strength and can be easily peeled off by applying voltage. Especially in the storage and use processes of parts, the anti-aging performance is excellent, the anti-impact performance is good, stripping can be conducted within a short time through a simple low-voltage device, no adhesive residue exists on a pasted object after stripping, and the defects in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape. Background Art

[0002] In the manufacturing process of electronic components of many 3C products, there are increasing demands for reprocessing to improve the yield rate and recycling of components after use. In order to meet these demands, adhesive solutions with certain adhesive strength and certain peelability are widely used in the fixing process of electronic components.

[0003] At present, the main physical solutions for easy peeling include easy-pull adhesives and easy-tear stickers. Among them, there is a risk of breakage in easy-pull adhesives, which makes it impossible to disassemble the parts, and the easy-tear sticker process is complicated and cumbersome. In addition to the above physical methods, there are also UV, solvent, heat, electricity and other methods to induce changes in the viscosity of adhesives, thereby achieving the effect of easy peeling. Among them, UV viscosity reduction is often used in transparent parts, solvent viscosity reduction has problems such as VOC, thermal viscosity reduction is often used in parts with high temperature resistance, and electrical viscosity reduction is a method of reducing the adhesion by applying voltage.

[0004] There are literature reports that by adding conductive salts to increase the conductivity of adhesives, when voltage is applied, the ions in the conductive salts will migrate to the bonding interface, weakening the bonding force and ultimately achieving an easy peeling effect. However, the above-mentioned electrolytic adhesive has poor bonding force before power is applied, and there will be obvious residues on the adhered object after power is applied and debonding. Summary of the invention

[0005] To solve the above problems, the present invention provides an electrolytic adhesive and its preparation method and application, and tape, which can improve the adhesion, holding force, shear force, cohesion, etc. of the electrolytic adhesive before power is applied, and reduce the residue on the adhered object after power is applied and debonding.

[0006] In a first aspect, the present invention provides an electrolytic adhesive, wherein the electrolytic adhesive is formed by copolymerization of a reactive conductive salt and a polymer monomer; Based on 100 parts by weight of the polymer monomer, the added amount of the reactive conductive salt is 0.5 to 25 parts by weight.

[0007] Furthermore, the reactive conductive salt is a reactive organic ionic liquid; the cation of the reactive organic ionic liquid is an imidazolium cation containing an allyl group, and the anion of the reactive organic ionic liquid includes Br - 、AlCl4 - 、Al2Cl7 - 、NO3 - 、BF4 - PF6 -、CH3COO - CF3COO - 、CF3CF2CF2COO - CF3SO3 - CF3(CF2)3SO3 - 、AsF6 - 、SbF6 - 、(FSO2)2N - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - 、(CF3SO2)3C - and F(HF)n - At least one of .

[0008] Furthermore, the chemical structural formula of the cation of the reactive organic ionic liquid is as shown in Formula I: The formula I: ; wherein at least one of R or R' contains an allyl functional group.

[0009] Furthermore, the chemical structural formula of the cation of the reactive organic ionic liquid is as shown in Formula II: The formula II: .

[0010] Furthermore, the polymer monomers include acrylate monomers and acrylic acid monomers, wherein the acrylate monomers include monomer units derived from acrylate having an alkyl group with 1 to 14 carbon atoms and acrylic acid monomer units derived from an alkyl group with 1 to 14 carbon atoms.

[0011] Furthermore, the polymer monomers also include monomers containing polar groups, and the polar groups include at least one of carboxyl groups, hydroxyl groups, cyano groups, amide groups, imide groups, amino groups, epoxy groups and anhydride groups.

[0012] Furthermore, based on 100 parts by weight of the polymer monomer, the total amount of the acrylate monomer and the acrylic acid monomer added is 70 to 98 parts by weight; based on 100 parts by weight of the polymer monomer, the amount of the monomer containing a polar group added is 2 to 30 parts by weight.

[0013] In a second aspect, the present invention provides a method for preparing the electrolytic adhesive according to any one of the first aspects, the preparation method comprising the following steps: The reactive conductive salt and the polymer monomer are copolymerized to obtain the electrolytic adhesive; The copolymerization reaction method includes a solution polymerization method; the working condition parameters of the solution polymerization method include: based on 100 parts by weight of the polymer monomer, the amount of solvent added is 100-500 parts by weight, and the amount of initiator added is 0.01-5 parts by weight; the reaction temperature is 60-85°C, and the reaction time is 3-20 hours. The solvent includes at least one of toluene, ethyl acetate and butanone, and the initiator includes at least one of a peroxide initiator and an azo initiator.

[0014] In a third aspect, the present invention provides a use of the electrolytic adhesive described in any one of the first aspect and the second aspect in preparing an adhesive tape.

[0015] In a fourth aspect, the present invention provides an adhesive tape comprising a release film and an electrolytic adhesive layer coated on the surface of the release film, wherein the electrolytic adhesive layer comprises the electrolytic adhesive and a curing agent as described in any one of the first aspect and the second aspect.

[0016] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art: The embodiment of the present invention provides an electrolytic adhesive and a preparation method and application thereof, and an adhesive tape. The electrolytic adhesive provided by the present invention has high adhesion and can be easily peeled off by applying voltage. In particular, during the storage and use of parts, it has excellent aging resistance and good impact resistance, can be peeled off in a short time with a simple low-voltage device, and no residual adhesive is left on the adhered object after peeling, which makes up for the shortcomings of the prior art. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0019] Electrolytic adhesives are based on the fact that when voltage is applied, the ions in the conductive salt inside the adhesive will migrate to the bonding interface, weakening the bonding force and ultimately achieving an easy peeling effect. However, the existing electrolytic adhesives have poor bonding strength before power is applied, and there will be obvious residues on the adhered object after power is applied and debonding.

[0020] In the existing electrolytic adhesive scheme, the adhesive and the conductive salt are physically mixed in a blending manner to achieve the electrolytic bonding effect. This physical blending method has a great impact on the adhesive's adhesion, holding force, shear force, etc., and the aging resistance is greatly reduced. The fixed parts are very likely to fall off during storage and use. After power-on peeling, due to the poor cohesion of the adhesive, there will be obvious residual adhesive on the adhered object.

[0021] To solve the above problems, the technical solution of the present invention is as follows: The invention provides an electrolytic adhesive and a preparation method and application thereof, and an adhesive tape, which are formed by copolymerization of a reactive conductive salt and a polymer monomer.

[0022] In the electrolytic adhesive, preparation method and application thereof, and adhesive tape of the present invention, the content of the reactive conductive salt is 0.5 to 25 parts by weight relative to 100 parts by weight of the polymer.

[0023] In the electrolytic adhesive, preparation method and application thereof, and adhesive tape of the present invention, the reactive conductive salt is a reactive organic ionic liquid.

[0024] In the electrolytic adhesive and its preparation method and application, and adhesive tape of the present invention, the cation of the reactive organic ionic liquid is preferably an imidazolium cation containing an allyl group, as shown in Formula I, wherein at least one of R or R' contains an allyl functional group, as shown in Formula II: Formula I (imidazolium cation): ; Formula II (1-allyl-3-methylimidazolium cation): .

[0025] In the electrolytic adhesive and its preparation method and application, and adhesive tape of the present invention, the anion of the reactive organic ionic liquid is preferably Br - 、AlCl4 - 、Al2Cl7 - 、NO3 - 、BF4 - PF6 - 、CH3COO - CF3COO - 、CF3CF2CF2COO - CF3SO3 - CF3(CF2)3SO3 - 、AsF6 - 、SbF6 - 、(FSO2)2N - 、(CF3SO2)2N - 、(CF3CF2SO2)2N- 、(CF3SO2)3C - and F(HF)n - One or more combinations of anionic compositions.

[0026] In the electrolytic adhesive, preparation method and application thereof, and adhesive tape of the present invention, the aforementioned polymer is preferably an acrylic (ester) polymer.

[0027] In the electrolytic adhesive, preparation method and application thereof, and adhesive tape of the present invention, the aforementioned polymer monomer, i.e., acrylic acid (ester) monomer, preferably includes a monomer unit derived from (meth) acrylic acid (ester) having an alkyl group with 1 to 14 carbon atoms. For example: CH2=C(R1)COOR2, wherein R1 is a hydrogen atom or a methyl group, and R2 is an alkyl group with 1 to 14 carbon atoms.

[0028] In the electrolytic adhesive and its preparation method and application, and adhesive tape of the present invention, the aforementioned polymer monomers also include monomers with polar groups, such as monomers containing carboxyl groups, monomers containing hydroxyl groups, monomers containing cyano groups, monomers containing amide groups, monomers containing imide groups, monomers containing amino groups, monomers containing epoxy groups, and monomers containing acid anhydride groups, etc. Among them, monomers containing carboxyl groups, monomers containing hydroxyl groups, and monomers containing amide groups are preferred, and they can be used alone or in combination.

[0029] In the electrolytic adhesive, preparation method and application thereof, and adhesive tape of the present invention, the content of the (meth) acrylic acid (ester) monomer having an alkyl group with 1 to 14 carbon atoms is 70 to 98 parts by weight relative to 100 parts by weight of all monomers constituting the acrylic acid (ester) polymer.

[0030] In the electrolytic adhesive, preparation method and application thereof, and adhesive tape of the present invention, the polar group monomer content is 2 to 30 parts by weight relative to 100 parts by weight of all monomers constituting the acrylic (ester) polymer.

[0031] In the electrolytic adhesive and its preparation method and application, and adhesive tape of the present invention, the electrolytic adhesive is formed by copolymerization of reactive conductive salt and polymer monomer, preferably by solution polymerization.

[0032] In the electrolytic adhesive, preparation method and application thereof, and tape of the present invention, the solvent used in the solution polymerization method is a mixture of one or more of toluene, ethyl acetate, butanone, etc., and the content of the solvent is 100-500 parts by weight relative to 100 parts by weight of all monomers constituting the above-mentioned acrylic (ester) polymer.

[0033] In the electrolytic adhesive, preparation method and application thereof, and tape of the present invention, the initiator used in the aforementioned solution polymerization method is a peroxide initiator, an azo initiator, etc., which can be used alone or in combination of multiple types. The content of the initiator is 0.01-5 parts by weight relative to 100 parts by weight of all monomers constituting the above-mentioned acrylic (ester) polymer.

[0034] In the electrolytic adhesive and its preparation method and application, and adhesive tape of the present invention, in the aforementioned solution polymerization method, the heating temperature is 60-85 degrees, and the heating reaction time is 3-20 hours.

[0035] In the electrolytic adhesive and its preparation method, application and adhesive tape of the present invention, isocyanate curing agent is preferably used as the curing agent of the electrolytic adhesive, and the content of the curing agent is 2-20 parts by weight relative to 100 parts by weight of all monomers constituting the above-mentioned acrylic (ester) polymer.

[0036] In the electrolytic adhesive and its preparation method and application, and the adhesive tape of the present invention, two layers of release films are used, the first release film is 50 μm thick and has a release force of 20-40 gf / in, the second release film is 25 μm thick and has a release force of 5-15 gf / in; the thickness of the electrolytic adhesive layer is 50 μm.

[0037] It should be noted that the electrolytic adhesive provided in the embodiments of the present invention, its preparation method and application, and the components and raw materials involved in the tape, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to existing processing techniques or directly using existing equipment, and the present invention document will not describe them one by one.

[0038] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0039] The sources of substances used in the examples of the present invention are as follows: Ethyl acrylate, AR, Shanghai Myrel Biochemical Technology Co., Ltd.; n-Butyl acrylate, AR, Shanghai Myrel Biochemical Technology Co., Ltd.; Acrylic acid, AR, Shanghai Myrel Biochemical Technology Co., Ltd.; Carboxyethyl acrylate, 98% (weight percent), Shanghai Myrel Biochemical Technology Co., Ltd.; 2-Hydroxyethyl methacrylate, 95% (weight percent), Shanghai Myril Biochemical Technology Co., Ltd.; Ethyl acetate, 99% (weight percent), Shanghai Myril Biochemical Technology Co., Ltd.; Toluene, AR, Sinopharm Chemical Reagent Co., Ltd.; Azobisisobutyronitrile (AIBN), CP, Sinopharm Chemical Reagent Co., Ltd.; Conductive salt, organic ionic liquid, 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 98%, Shanghai Myrel Biochemical Technology Co., Ltd.; Isocyanate curing agent, TPA100, Asahi Kasei.

[0040] Example 1 This embodiment provides an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 10 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 38.7% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0041] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 38.7 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days to obtain the electrolytic adhesive tape of Example 1.

[0042] The first release film used in this embodiment has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0043] Example 2 This embodiment provides an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 5 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 37.6% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0044] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 37.6 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days, thereby obtaining the electrolytic adhesive tape of Example 2.

[0045] The first release film used in this embodiment has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0046] Example 3 This embodiment provides an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 15 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 39.7% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0047] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 39.7 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days, thereby obtaining the electrolytic adhesive tape of Example 3.

[0048] The first release film used in this embodiment has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0049] Example 4 This embodiment provides an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 20 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 40.8% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0050] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 40.8 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days, thereby obtaining the electrolytic adhesive tape of Example 4.

[0051] The first release film used in this embodiment has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0052] Example 5 This embodiment provides an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 25 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 41.7% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0053] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 41.7 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days, thereby obtaining the electrolytic adhesive tape of Example 5.

[0054] The first release film used in this embodiment has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0055] Example 6 This embodiment provides an electrolytic adhesive, a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 30 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 42.7% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0056] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 42.7 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days, thereby obtaining the electrolytic adhesive tape of Example 6.

[0057] The first release film used in this embodiment has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0058] Comparative Example 1 This comparative example adopts a physical mixing method to prepare an electrolytic adhesive, comprising the following steps: 1. Synthesis of adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.4 parts by weight of an initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 5 hours to obtain an adhesive. The obtained adhesive contained 36.5% by weight of an acrylic acid (ester) copolymer.

[0059] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent and 10 parts by weight of organic ionic liquid 1-allyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt were added to 100 parts by weight of the electrolytic adhesive (including 36.5 parts by weight of acrylic acid (ester) copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film and o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days to obtain the electrolytic adhesive tape of Comparative Example 1.

[0060] The first release film used in this comparative example has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0061] Comparative Example 2 This comparative example provides an electrolytic adhesive and a preparation method and application thereof, and an adhesive tape, comprising the following steps: 1. Synthesis of electrolytic adhesive A monomer mixture consisting of 20 parts by weight of ethyl acrylate, 70 parts by weight of n-butyl acrylate, 5 parts by weight of acrylic acid, and 5 parts by weight of 2-hydroxyethyl methacrylate and 175 parts by weight of a solvent (ethyl acetate: toluene (weight ratio) = 8:2) were put into a round-bottom flask, and after replacing the air with nitrogen (purity 99.9%), 0.2 parts by weight of initiator azobisisobutyronitrile (AIBN) was added, and the temperature was raised to 85 degrees for reaction for 2 hours, and then 40 parts by weight of 1-allyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt and 0.2 parts by weight of initiator azobisisobutyronitrile were added, and the reaction was continued at 85 degrees for 3 hours to obtain an electrolytic adhesive. The obtained electrolytic adhesive contains 44.5% by weight of reactive ionic liquid and acrylic acid (ester) copolymer.

[0062] 2. Preparation of electrolytic adhesive tape 5.0 parts by weight of isocyanate curing agent was added to 100 parts by weight of the electrolytic adhesive (including 44.5 parts by weight of the electrolytic adhesive copolymer), mechanically stirred at room temperature for 15 minutes, and allowed to stand for degassing to obtain an electrolytic adhesive mixture. The obtained electrolytic adhesive mixture was coated on the first release film. o C oven for 5 minutes; cover the coated film with the second release film, and then place it at 40 o C for 3 days, thereby obtaining the electrolytic adhesive tape of Comparative Example 2.

[0063] The first release film used in this comparative example has a thickness of 50 μm and a release force of 30 gf / in, the second release film has a thickness of 25 μm and a release force of 10 gf / in; and the thickness of the electrolytic adhesive layer is 50 μm.

[0064] Test Case In this example, the electrolytic adhesives obtained from the above examples and comparative examples were subjected to performance tests.

[0065] 1. Peel force test The second release film of the electrolytic adhesive tape is peeled off and pasted on an aluminum foil (substrate) with a thickness of 50 μm. After pasting the aluminum foil, cut the bonded sample into test strips with a length of 250 mm × 25 mm (3 test strips for each embodiment and comparative example). Peel off the first release film of the cut test strips and paste them on a stainless steel plate (object to be adhered). Use a 2kg rubber roller to reciprocate three times along the long side direction of the test strip at a speed of 300 mm / min, thereby making a test sample of the adherend, the electrolytic adhesive layer and the substrate. After standing for 30 minutes, use a tensile testing machine to test 180 at a speed of 300 mm / min. o The peel force of each sample is measured by taking the average value of the test data of each sample as the measured value.

[0066] 2. Test of peeling force with power on The sample was prepared as above. After the prepared test sample was left to stand for 30 minutes, a voltage of 10V was applied for 10 seconds. Then, a tensile tester was used to test the sample for 180° under the voltage. o Peel force (tensile speed: 300 mm / min).

[0067] 3. Peelability evaluation The peelability of the electrolytic adhesive is evaluated by the degree of reduction in peel force (reduction rate) after voltage is applied. The reduction rate is calculated as follows.

[0068] Reduction rate = (peel force without voltage applied - peel force after voltage applied) / peel force without voltage applied × 100% When the reduction rate is 80% or more, peeling can be easily achieved by applying voltage. When the reduction rate is greater than 50% and less than 80%, peeling is possible. When the reduction rate is less than 50%, peeling is difficult.

[0069] 4. Evaluation of residual adhesive By observing whether there is any adhesive residue on the surface of the attached object after peeling, the case where the adhesive residue is on the surface of the attached object is judged as "there is adhesive residue", and the case where no adhesive is found on the surface of the attached object is judged as "no adhesive residue".

[0070] 5. High temperature retention The sample was prepared as above. The 25 mm wide test strip was pasted on the stainless steel plate. The bonding area was 25 mm × 25 mm. The counterweight was 1 kg. The test temperature was 85 o C, record the time when the sample falls off the stainless steel plate.

[0071] The test results are shown in Table 1.

[0072] Table 1 Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Acrylic acid monomer weight parts 100 100 100 100 100 100 100 100 Ionic liquid weight 10 5 15 20 25 30 10 40 Curing agent weight 5 5 5 5 5 5 5 5 Peeling force before power on (N / 25mm) 24 26 22 20 20 18 8 12 Peeling force after power on (N / 25mm) 1 3 1 2 1 1 2 1 Reduction rate (%) 95.8 88.5 95.5 90.0 95.0 94.4 75.0 91.7 Residual glue (peeled off after power on) No residual glue No residual glue No residual glue No residual glue No residual glue No residual glue There is residual glue No residual glue High temperature retention (hour) >24 >24 >24 >24 >24 >24 <1 3 It can be seen from Table 1 that the peeling force before power-on in the embodiments is above 18 N / 25 mm, which can meet the requirements for fixing and bonding most electronic components.

[0073] It can be seen from Examples 1-6, Comparative Example 2 and Comparative Example 1 that when the amount of organic ionic liquid added to the electrolytic adhesive prepared by the physical blending method is only 10 parts by weight, the peeling force has been reduced to 8N. The use of reactive organic ionic liquid and acrylic monomer copolymerization can greatly improve the peeling force of the electrolytic adhesive and has a good electrified glass effect. However, when the amount of organic ionic liquid added reaches 40 parts by weight, the peeling force is reduced to 12N, and the high temperature retention force is only 3 hours.

[0074] It can be seen from Examples 1 and 2 that reducing the weight of the ionic liquid can improve the peeling force, but the electrolytic bonding effect will be reduced.

[0075] It can be seen from Examples 1-6 that the electrolytic adhesive synthesized by copolymerization of reactive organic ionic liquid and acrylic acid monomer has no residual adhesive after power-on peeling, and the high temperature retention is more than 24 hours.

[0076] In summary, the present invention provides an electrolytic adhesive and its preparation method and application, and an adhesive tape. The present invention uses a copolymerization reaction between a reactive organic ionic liquid and an acrylic acid (ester) monomer, and the electrolytic adhesive synthesized by this method has high adhesion and can be easily peeled off by applying a voltage. Especially during the storage and use of parts, it has excellent aging resistance and good impact resistance, and can be peeled off in a short time with a simple low-voltage device, and there is no residual adhesive on the adhered object after peeling.

[0077] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0078] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. An electrolytic adhesive, characterized in that: The electrolytic adhesive is formed by copolymerization of reactive conductive salt and polymer monomer; Based on 100 parts by weight of the polymer monomer, the added amount of the reactive conductive salt is 0.5 to 25 parts by weight.

2. The electrolytic adhesive according to claim 1, characterized in that: The reactive conductive salt is a reactive organic ionic liquid; the cation of the reactive organic ionic liquid is an imidazolium cation containing an allyl group, and the anion of the reactive organic ionic liquid includes Br - 、AlCl4 - 、Al2Cl7 - 、NO3 - 、BF4 - PF6 - 、CH3COO - CF3COO - CF3CF2CF2COO - CF3SO3 - CF3(CF2)3SO3 - 、AsF6 - 、SbF6 - 、(FSO2 )2 N - 、(CF3SO2)2N - 、(CF3CF2SO2)2N - 、(CF3SO2)3C - and F(HF)n - At least one of .

3. The electrolytic adhesive according to claim 2, characterized in that: The chemical structural formula of the cation of the reactive organic ionic liquid is shown in Formula I: The formula I: ; wherein at least one of R or R' contains an allyl functional group.

4. The electrolytic adhesive according to claim 2, characterized in that: The chemical structural formula of the cation of the reactive organic ionic liquid is shown in Formula II: The formula II: .

5. The electrolytic adhesive according to any one of claims 1 to 4, characterized in that: The polymer monomers include an acrylate monomer and an acrylic acid monomer. The acrylate monomer includes a monomer unit derived from an acrylate having an alkyl group with 1 to 14 carbon atoms and an acrylic acid monomer unit derived from an alkyl group with 1 to 14 carbon atoms.

6. The electrolytic adhesive according to claim 5, characterized in that: The polymer monomer further comprises a monomer containing a polar group, wherein the polar group comprises at least one of a carboxyl group, a hydroxyl group, a cyano group, an amide group, an imide group, an amino group, an epoxy group and an anhydride group.

7. The electrolytic adhesive according to claim 6, characterized in that: Based on 100 parts by weight of the polymer monomer, the total amount of the acrylate monomer and the acrylic acid monomer added is 70 to 98 parts by weight; based on 100 parts by weight of the polymer monomer, the amount of the monomer containing a polar group added is 2 to 30 parts by weight.

8. A method for preparing the electrolytic adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The reactive conductive salt and the polymer monomer are copolymerized to obtain the electrolytic adhesive; The copolymerization reaction method includes a solution polymerization method; the working condition parameters of the solution polymerization method include: based on 100 parts by weight of the polymer monomer, the amount of solvent added is 100-500 parts by weight, and the amount of initiator added is 0.01-5 parts by weight; the reaction temperature is 60-85°C, and the reaction time is 3-20 hours. The solvent includes at least one of toluene, ethyl acetate and butanone, and the initiator includes at least one of a peroxide initiator and an azo initiator.

9. Use of the electrolytic adhesive according to any one of claims 1 to 8 in the preparation of an adhesive tape.

10. An adhesive tape, characterized in that: The adhesive tape comprises a release film and an electrolytic adhesive layer coated on the surface of the release film, wherein the electrolytic adhesive layer comprises the electrolytic adhesive according to any one of claims 1 to 8 and a curing agent.